Development of a proof-of-concept spectropolarimeter in the framework of the GSST mission: Characterization and performance analysis of a sCMOS image sensor - Rodrigues Barbosa, Adriany; Carlesso, Franciele; Vieira, Luis Eduardo Antunes (Frontiers in Astronomy and Space Sciences, 2022)
Camera characterization is critical for solar observation instruments such as spectropolarimeters. This paper presents the characterization of the proof-of-concept spectropolarimeter sCMOS image sensor. The report is divided into two parts. The first is to analyze the behavior of each pixel due to changes in the camera’s operation mode. Analyze the camera’s sensor cooling, shutter, and corrections and filters. The second part is the characterization of the camera, analyzing linearity, gain, and polarization effects. For this first phase of the project, the commercial sCMOS image sensor successfully acquired images of the Stokes parameters in an agile manner. However, a new camera with less non-linearity will be necessary for the project’s next phase.